DEVELOPING AND VALIDATING A SCALE TO MEASURE FOOTBALL TEAM LOVE - Caner Özgen (International Journal of Management Studies)
Previous studies in sports marketing have shown that team love is a key factor influencing loyalty, satisfaction and positive word-of-mouth behaviours. Despite these positive findings, research on team love remains limited, and the concept’s theoretical framework is underdeveloped. The study aims to conceptualize football team love using a grounded theory approach and to develop a scale based on this conceptualization. Through a comprehensive literature review, as well as data obtained from focus group and in-depth interviews with football fans, the study delineated the unique conceptual dimensions of team love. Using data obtained from 452 Turkish football fans, exploratory factor analysis (EFA) revealed a three-dimensional (self-team integration, infinity, and passion-driven behaviours), 12-item structure. Confirmatory factor analysis (CFA) further validated and refined, a three-dimensional, nine-item measurement model. This research provides an in-depth, theory-based understanding of the unique construct of football team love, offering valuable insights for both academic and practical applications. The findings lay a foundation for further research and provide strategic guidance for sports marketers to foster stronger connections between football teams and their fans.